Qualitative and quantitative changes in lipids of cowpea (Vigna unguiculata): Impact of changes in seed vigour - SHAHEEN, RESHMA; SRINIVASAN, KALYANI; UMAR, SHAHID; SUNEJA, POONAM; YADAV, SANGITA (The Indian Journal of Agricultural Sciences, 2013)
Seeds of cowpea (Vigna unguiculata L. Walp.) varieties (V 240, V 578 and V 585) were subjected to controlledageing experiment and subsequently were divided into high, medium and low vigour categories depicting 24, 72 and 120hr ageing. The lipid content, fatty acid profile and lipid peroxidation determinations were performed. Changes in seedvigour impacted lipid content where the lowest lipid content was displayed by low vigour seeds being more drastic in V3but moderate in V1 and V2. Regarding fatty acid composition, both palmitic and stearic acids contents significantlyincreased in low seed vigour category in V2 and V3; however, in V3, there was no significant difference between variousvigour categories. Similarly, stearic acid content V1, V2 and V3 displayed significant increase in the low vigour categories;whereas, increased oleic acid content in the medium and low vigour lots was evident in V1 and V2 while in V3 where thelow vigour lot exhibited significantly lower content as compared to the control. A comparatively smaller proportion ofarachidic acid was evident which also increased significantly as quality dropped in V1 consistent increase was not observedin V2, V3. The content of two unsaturated fatty acids namely linoleic and linolenic acid was differential in varieties tested.Lipid peroxidation value of the three varieties exhibited a concomitant increase with decrease in vigour thus registeringthe highest value in the seeds with poorest seed quality.